2016
DOI: 10.18632/oncotarget.7999
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated S100P protein binds and inactivates p53, permits therapy-induced senescence and supports chemoresistance

Abstract: S100P belongs to the S100 family of calcium-binding proteins regulating diverse cellular processes. Certain S100 family members (S100A4 and S100B) are associated with cancer and used as biomarkers of metastatic phenotype. Also S100P is abnormally expressed in tumors and implicated in migration-invasion, survival, and response to therapy. Here we show that S100P binds the tumor suppressor protein p53 as well as its negative regulator HDM2, and that this interaction perturbs the p53-HDM2 binding and increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…S100P also binds p53, together with its negative regulator HDM2, and perturbs the p53-HDM2 complex binding and increases the p53 level. However, the S100P-induced p53 is not able to activate its transcriptional targets (e.g., hdm2, p21WAF, and bax) following the DNA damage and enhances chemoresistance by binding and inactivating p53 (35). In contrast to the above findings, studies on ovarian cancer cells show a chemo-sensitization effect of S100P in response to drugs including carboplatin and paclitaxel, 5-fluorouracil, etoposide, and doxorubicin (32).…”
Section: Introductionmentioning
confidence: 81%
“…S100P also binds p53, together with its negative regulator HDM2, and perturbs the p53-HDM2 complex binding and increases the p53 level. However, the S100P-induced p53 is not able to activate its transcriptional targets (e.g., hdm2, p21WAF, and bax) following the DNA damage and enhances chemoresistance by binding and inactivating p53 (35). In contrast to the above findings, studies on ovarian cancer cells show a chemo-sensitization effect of S100P in response to drugs including carboplatin and paclitaxel, 5-fluorouracil, etoposide, and doxorubicin (32).…”
Section: Introductionmentioning
confidence: 81%
“…Mutant p53, mostly missense mutations in exons 4–9, possesses a gain-of-function involving in tumorigenesis, invasion and metastasis66. Several members of S100 family can directly bind to p53 and inhibit expression and phosphorylation of p53, which promotes stemness of cancer cells, contributes to chemoresistance and leads to cancer progression6768697071. Otherwise, S100A4 may interact with mutant-type p53 and promote its accumulation in cancer cells32.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, recent data suggest that therapy-induced senescence (TIS) can lead to cancer recurrence in patients subjected to radio/chemotherapy. [15][16][17]19,[39][40][41] Therefore, we studied induction of senescence by clinically used chemotherapeutics in human HCT116 and SW480 colon cancer cells in vitro. In the present study we showed that DOXO, IRINO or 5-FU treatment of colon cancer cells leads to accumulation of senescent cells exhibiting several features of stemness.…”
Section: Discussionmentioning
confidence: 99%